Endocrine effects of three common gas signaling molecules in humans: A literature review - Qi, Wei; Man, Luo; Suguro, Sei; Zhao, Yidan; Quan, Heng; Huang, Chuoji; Ma, Haoran; Guan, Haoran; Zhu, Yizhun (Frontiers in Endocrinology, 2022)
Gases such as hydrogen sulfide, nitric oxide and sulfur dioxide have important regulatory effects on the endocrine and physiological processes of the body and are collectively referred to as "gas signaling molecules". These gas signaling molecules are also closely related to Alzheimer's disease, the inflammatory response and depression. In this paper, we introduce the production and metabolic pathways of NO, H2S and SO2 in living organisms and review the regulatory functions of gas signaling molecules in the endocrine system and their mechanisms in relation to their clinical applications. This work will provide a basis for finding targets for intervention and establishing novel prevention and treatment strategies for related diseases.